A better IDEA: best practice and outcomes‐oriented remedies in public impact litigation for students with disabilities. Issue 3 (19th June 2014) - Noonan, Kathleen G.; McCarthy, Megan A.; Shea, Lindsay; Marcus, Steven C.; Mandell, David S.
Abstract : Class action lawsuits filed in violation of Individuals with Disabilities Education Act (IDEA) raise questions for those concerned with improving the education system for students with disabilities. First, do the lawsuits result in changes that can be directly linked to improved student outcomes? Second, do these lawsuits and the 'consent decrees' that settle them refer to best practices in educating children with disabilities? To date, no study has examined the remedies ordered as a result of these lawsuits in the disability education context, or proven how different types of remedies can impede or facilitate progress for students with disabilities. Class action lawsuits under IDEA filed in large, urban school districts between 1990 and 2011 and the remedies ordered under the final agreement were reviewed. This review suggests that the lawsuits against large, urban school districts tend to result in remedial activities that focus more on planning, supporting and monitoring than on outcomes or evidence‐based practice.